Changes in Blood Pressure of Hypertension Patients With Therapy Non Pharmacological Use of Celery Leaves - Olgrid Algarini Allo; Adriana Mapandin; Junelty Almar; Tasya Gratia Ginur (International Journal of Health and Social Behavior, 2024)
Background High blood pressure or hypertension is one of the biggest causes of death in the world. Adopting a healthy lifestyle can prevent or slow the onset of hypertension and reduce cardiovascular risk Apiin and mannitol content in celery leaves have diuretic properties that help draw fluid and support kidney function in removing excess fluid from the body. This process can significantly lower blood pressure in people with hypertension Objectives to determine changes in blood pressure in hypertensive patients with non-pharmacological therapy using celery leaves Quasi-Experimental design method with Pre-test and Post-test control group design. Samples were taken using Purposive Sampling technique as many as 30 people Research Results From the characteristics of respondents and based on statistical tests with the Wilcoxon Test in the intervention group Pre-test Post-test obtained Asymp. Sig. value of 0.890 Conclusion There is no significant change between the intervention group and the control group in the provision of non-pharmacological therapy using Celery leaves Suggestions For people with hypertension to always seek information in improving self-management in order to reduce the risk of cardiovascular diseases such as hypertension.